2017
DOI: 10.1161/circimaging.117.006446
|View full text |Cite
|
Sign up to set email alerts
|

Denervated Myocardium Is Preferentially Associated With Sudden Cardiac Arrest in Ischemic Cardiomyopathy

Abstract: Background Previous studies have identified multiple risk factors that are associated with total cardiac mortality. Nevertheless, identifying specific factors that distinguish patients at risk of arrhythmic death versus heart failure could better target patients likely to benefit from implantable cardiac defibrillators (ICDs), which have no impact on non-sudden cardiac death (NSCD). Methods and Results We performed a pilot competing risks analysis of the NIH-sponsored PAREPET trial (Prediction of ARrhythmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The adverse effects of obesity on cardiovascular haemodynamics, structure, impaired systolic and/or diastolic ventricular function, and increased risk of cardiac failure have been widely reported 24 , 25 . Increased obesity-related cardiac output, metabolic dysregulation, myocardial fatty infiltration all contribute to the eccentric and concentric hypertrophy characteristic of obesity-related cardiac failure 26 , which is also a cause of cardiogenic arrest 27 . Our results demonstrated a quasi-higher percentage of inotrope use in the overweight (76%) and obese patients (91%), as well as higher percentage of ECMO use (60%) in the obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects of obesity on cardiovascular haemodynamics, structure, impaired systolic and/or diastolic ventricular function, and increased risk of cardiac failure have been widely reported 24 , 25 . Increased obesity-related cardiac output, metabolic dysregulation, myocardial fatty infiltration all contribute to the eccentric and concentric hypertrophy characteristic of obesity-related cardiac failure 26 , which is also a cause of cardiogenic arrest 27 . Our results demonstrated a quasi-higher percentage of inotrope use in the overweight (76%) and obese patients (91%), as well as higher percentage of ECMO use (60%) in the obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent data analysis showed that while a larger LVEDVI, lack of angiotensin inhibition therapy, and elevated BNP enhanced the association of high-risk image findings with an arrhythmic event, a higher resting heart rate, older age, elevated creatinine, a larger left atrial volume index and a larger LVEDVI better predicted non-sudden cardiac death. 20 Thus, combining image data with cardiac and clinical parameters improves identification of patients likely to benefit from an ICD.…”
Section: Advantages Of Radionuclide Cardiac Autonomic Innervation Imamentioning
confidence: 99%
“…Nerve sprouting may promote the heterogeneity of excitability and refractoriness, which was suggested to increase arrhythmia susceptibility in the reinnervated infarct border zone [8,9]. However, recent clinical studies [10,11] have shown that cardiac sympathetic denervation (rather than reinnervation) can lead to a higher risk of ventricular arrhythmias and arrhythmic death. Experimental and computational studies linked the beneficial effect of innervation to attenuation of infarct-induced vulnerability to repolarisation alternans via β-adrenergic activation [12,13] or to reduction of electrophysiological heterogeneity and calcium mishandling, which was present even when the nerves were not activated [14].…”
Section: Introductionmentioning
confidence: 99%